Pengaruh Audit Tenure, Ukuran KAP dan Ukuran Perusahaan terhadap Opini Going Concern - Atha Alhady Rafi; Nasrizal Nasrizal; Fitri Humairoh (Penerbit Goodwood, 2024)
Purpose: This study examines and analyzes the influence of Audit Tenure, Size of Public Accounting Firm (KAP), and company size on audit opinion regarding going concerns. Methodology/Approach: This hypothesis testing employs logistic regression analysis conducted with the assistance of SPSS 25 software. Results/Findings: Audit tenure has a negative effect on the acceptance of going-concern audit opinions; thus, H1 is accepted. The variable size of the audit firm has a negative effect on the acceptance of going-concern audit opinions; hence, H0 is rejected. The size of the company variable does not affect the acceptance of the going-concern audit opinion; therefore, H0 is rejected. Limitations: The limitations of the study include challenges in resources, such as time and cost, which may restrict the ability to extend the generalization of results comprehensively. Investigating additional variables, such as company growth, profitability, and the previous year's audit opinion, may lead to limitations in measurement and variable control. Contribution: This study contributes to the understanding of the factors that influence going-concern audit opinions.